ANALYSIS OF FACTORS ASSOCIATED WITH THE IMPLEMENTATION OF SEX EDUCATION AMONG ELEMENTARY SCHOOL CHILDREN IN RURAL AREAS - Lasiyati Yuswo Yani (Universitas STRADA Indonesia, 2024)
Early sex education for children is very important to prevent sexual violence, but many parents believe that sex education for children is taboo. This research aims to find out what factors are related to parents' sex education practices for elementary school children. This research was conducted at Rural area. This research is descriptive analytical with a cross sectional approach. The population in this study were parents of students. The sample was selected using a purposive sampling method resulting in 171 respondents. Data collection uses a questionnaire. The data analysis SPSS. The conclusion of this research, factors related to the implementation of parental sex education for elementary school children the first factor is parents' education and age, the second factor is parents' knowledge, and the third factor is parents' experience. The parents will increase information about early sex education for children, so that parents have good knowledge about sex education.